ANGKUTAN UDARA PERINTIS SEBAGAI JEMBATAN UDARA MENUNJANG PERTUMBUHAN EKONOMI DAERAH - Budi Prasetyo; Sunarno; Solihin (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Indonesia is an archipelagic country and the distance between islands requires a distance that is not easily traveled to connect the inhabitants' economic life system paths to one island and another, this requires facilities that can bridge this issue through air transportation, where multiflier effects are very significant for life economy of remote areas in Indonesia.